Carbon‐Dot‐Sensitized, Nitrogen‐Doped TiO2 in Mesoporous Silica for Water Decontamination through Nonhydrophobic Enrichment–Degradation Mode. Issue 49 (21st October 2015) - Cheng, Chen; Tan, Xianjun; Lu, Deli; Wang, Lingzhi; Sen, Tapas; Lei, Juying; El‐Toni, Ahmed Mohamed; Zhang, Jinlong; Zhang, Fan; Zhao, Dongyuan
Abstract: Mesoporous silica synthesized from the cocondensation of tetraethoxysilane and silylated carbon dots containing an amide group has been adopted as the carrier for the in situ growth of TiO2 through an impregnation–hydrothermal crystallization process. Benefitting from initial complexation between the titania precursor and carbon dot, highly dispersed anatase TiO2 nanoparticles can be formed inside the mesoporous channel. The hybrid material possesses an ordered hexagonal mesostructure with p 6 mm symmetry, a high specific surface area (446.27 m 2 g −1 ), large pore volume (0.57 cm 3 g −1 ), uniform pore size (5.11 nm), and a wide absorption band between λ =300 and 550 nm. TiO2 nanocrystals are anchored to the carbon dot through TiON and TiOC bonds, as revealed by X‐ray photoelectron spectroscopy. Moreover, the nitrogen doping of TiO2 is also verified by the formation of the TiN bond. This composite shows excellent adsorption capabilities for 2, 4‐dichlorophenol and acid orange 7, with an electron‐deficient aromatic ring, through electron donor–acceptor interactions between the carbon dot and organic compounds instead of the hydrophobic effect, as analyzed by the contact angle analysis. The composite can be photocatalytically recycled through visible‐light irradiation after adsorption. The narrowed band gap, as a result of nitrogen doping, and the photosensitization effect of carbon dots are revealed to be coresponsible for the visible‐light activity of TiO2 . The adsorption capacity does not suffer any clear losses after being recycled three times. Abstract : Trapped in channels : Mesoporous silica synthesized from the cocondensation of tetraethoxysilane and silylated carbon dots (CDs) containing an amide group has been adopted as the carrier for the in situ growth of TiO2 . This composite shows excellent adsorption capabilities for 2, 4‐dichlorophenol (2, 4‐DCP; see figure) and acid orange 7.